Determinan Minat Beli Produk Makanan Kemasan Halal dalam Perspektif Milenial - Jasman, Zahra Ramadani; Halim, Ichsan Jamil; Zuhdi, Muhammad; Albigaeri, Syahruly Nizar (Universitas Islam Internasional Darullughah Wadda'wah, 2023)
.The halal label is a label placed on the packaging which indicates that a product has undergone a halal inspection process and has been declared halal by the Halal Product Guarantee Organizing Agency and the Majelis Ulama Indonesia. This research aims to explain the determinants of consumer buying interest in halal products which are generated by the independent variable on the dependent variable, namely the significant influence between halal certification and halal awareness. This research uses quantitative research with a research sample of 91 respondents. The data analysis technique consists of classical assumption testing, multiple linear regression analysis and hypothesis testing using the SPSS 26 program. The results of this research show that the halal certification variable partially influences purchase interest with a significance value of 0.015 > 0.05. Meanwhile, the halal awareness variable is also stated to have an influence on buying interest. This is supported by the results obtained with a significance level of 0.000 < 0.05